Advances in Decision Making - Pedro García Márquez, Fausto (IntechOpen, 2022)
This book presents a comprehensive overview of the principles and practices of decision-making. It highlights the interface between engineering/technology and the organizational, administrative, and planning abilities of decision-making. The chapters address decision-making using real-world case studies. They also discuss decision-making theory as well as relevant analysis techniques. The book blends computational techniques, dynamic analysis, probabilistic methods, and mathematical optimization techniques to support the analysis of multi-criteria decision-making problems with defined constraints and requirements.